Historical dictionary of gothic literature - Hughes, William (Historical dictionaries of literature and the arts., 2013)
Provides an extensive chronology and an introduction which explains the nature of Gothic and shows how it has evolved. Includes entries on major writers, and works of geographical variants like Irish, Scottish or Russian Gothic and Female Gothic, Queer Gothic and Science Fiction.